The Influence Of Booklet And Video On Knowledge And Posyandu Cadres' Attitudes Regarding Stunting In The Area Pb Selayang II Puskesmas Works In 2023 - Lailan Syafrina Lubis; Daniel Ginting; Frida Lina Tarigan (Jurnal Info Sains : Informatika dan Sains, 2023)
Stunting is a condition of toddlers who have a long or Height is less compared to his age. Objective This research is to determine the effect of booklets and videos on knowledge and attitudes of posyandu cadres regarding stunting in the work area PB Selayang II Medan Community Health Center in 2023. Type of research used is quantitative research with a quasi-experimental design through a non-experimental design equivalent control group. The research sample consisted of 136 posyandu cadres. Data analyzed using the Paired t test. The results of research tests show that there is the difference in the mean value of cadre knowledge before (58.81) and after (70.24) as well students' attitudes before (48.95) and after (67.96) being given the intervention media booklet with a value of p=0.000, then there is also a difference in the average value of knowledge cadres before (59.14) and after (73.76) as well as student attitudes before (46.79) and afterward (67.35) were given video media intervention with p=0.000. But at the end research shows that video media has more influence on knowledge (73.76) and attitude (67.35) of cadres regarding stunting. Based on this, it is recommended to the Puskesmas to use booklets and videos as media health promotion in conveying information about stunting so that it can Efforts are made to prevent stunting.